DUSUN EDUCATION: âSEBAGAI STRATEGI PENEKANAN TINDAK KRIMINAL MELALUI RAMBU-RAMBU MORAL DI DESA DUKUHWALUH KECAMATAN KEMBARAN KABUPATEN BANYUMAS - Janah, Felistya Aprili Baeti; Setiana, Desti Dwi; Mistialim, Balkis (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
Dukuhwaluh village located in the district of Banyumas twins has a strategic location because it is close to educational facilities such as Muhammadiyah University of Purwokerto, and educational institutions at the high school, junior high, elementary and early childhood education. The number of educational facilities should be able to encourage the distribution of better science, so that science is not only channeled directly to the educational actors alone, but able to give a positive impact to the surrounding community. But in fact the people in the village Dukuhwaluh still less awareness about education. Number of children who drop out of school so that trigger high unemployment, crime often triggers. Therefore, we moved to this situation to give an effort to improve the moral crisis through the program "Dusun Education", so that people have the knowledge to create awareness behave and act according to the rules and norms prevailing in the community, through a simple but effective learning in educating citizens. Methods of implementation of the "Dusun Education" is to provide socialization, education about crime, the study of spirituality, entrepreneurship training, motivational training, and installation-signpost signpost motivation as moral guidelines. With the implementation of all activities "Hamlet Education" will benefit the community, which is increasing the quality of education, hygiene, and safety in the village Dukuhwaluh, increasing citizens awareness of the importance of pressing crime, declining crime occurred, as well as the activities of the youth who had started the vacuum again.